Export processing in the Caribbean : the Jamaican experience. - WILLMORE, Larry (1994)
Reports on a case study of Jamaica's use of export processing for industrial development. Argues that benefits to Jamaica are reduced by policies that confine exporters to economic enclaves and limit their contact with the rest of the economy.